Analysis of ground settlement accelerated by vertical drains - Yeoh, Kiang Meng (2018)
Over the past decades, expansion of buildings and infrastructures to coastal and near-shore regions using land reclamation has become a common practice in many countries. The seabed along the shorelines of these regions typically consist of thick marine sediments. The hydraulic fill is likely to be the most economic method of construction. Sometimes excavated soft soil from construction sites is used for land reclamation. Therefore ground treatment is required to accelerate the consolidation process of the soft marine clay layer and also increase the bearing capacity of the reclamation land. There are various methods of ground improvement for soft clays for light or flexible structures. One of the favourite techniques is using the vertical drains which have a distinct advantage of faster rate of consolidation. However, for the high rise building structures which are very sensitive to the ground settlement, piling techniques are recommended. In this investigation, the consolidation characteristics of soft clay with vertical drains and surcharge ground treatment in reclamation projects are analysed using theoretical and field observation techniques. Three case studies namely, the Chek Lap Kok International Airport, Kansai International Airport and Changi Airport are included in this investigation. The investigation for the Chek Lap Kok International Airport is limited to the Test Embankment where PVDs of different spacing are installed and through the Upper Marine Clay layer. The computed result shows a slow rate of consolidation when the PVDs are spaced further apart. The Kansai Airport is located at the Osaka Bay. The geological profile of the Osaka Bay is made up of numbers of clay and sand layers. The 40 cm diameter vertical sand drains which completely penetrate the Holocene marine clay layer are installed using the displacement type method. The result shows good prediction on the magnitude of the final settlement, when the degree of consolidation is relatively high (e.g. U > 70%). The investigation for the Changi International Airport is limited to the Pilot test area where PVDs of 1.5 m x 1.5 m spacing are installed and penetrated through the Upper Marine Clay layer. The prediction shows the magnitude of the final settlement is greatly affected by the degree of consolidation of the measured settlement values. When comparing the ground treatment with vertical drains, a lower rate of consolidation is observed for the PVD untreated area. This shows that the consolidation of soft clays below the reclamation fills can be accelerated by vertical drains. Both the Asaoka Method and the hyperbolic method have been evaluated for all the three case studies and found to work extremely well in the prediction of the final field settlement. The evaluation of the Terzaghi one dimensional consolidation method and VDrainSt also found these two methods worked very well in predicting the ultimate consolidation settlement. However, if the actual soil parameters are not precisely obtained, the accuracy of the results will be affected.